2017
DOI: 10.1007/s11065-017-9363-3
|View full text |Cite
|
Sign up to set email alerts
|

The Efficacy of Cognitive Intervention in Mild Cognitive Impairment (MCI): a Meta-Analysis of Outcomes on Neuropsychological Measures

Abstract: Cognitive training in MCI may stimulate pre-existing neural reserves or recruit neural circuitry as “compensatory scaffolding” prompting neuroplastic reorganization to meet task demands (Reuter-Lorenz & Park, 2014). However, existing systematic reviews and meta-analytic studies exploring the benefits of cognitive interventions in MCI have been mixed. An updated examination regarding the efficacy of cognitive intervention in MCI is needed given improvements in adherence to MCI diagnostic criteria in subject sel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
180
1
12

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 218 publications
(199 citation statements)
references
References 142 publications
(167 reference statements)
6
180
1
12
Order By: Relevance
“…One low‐quality, exploratory study evaluated cognitive rehabilitation for improving cognitive impairment in PD patients receiving computer‐based cognitive training; some significant effects were reported. Because of the exploratory character of the study and the small sample size, the efficacy conclusion is “ insufficient evidence .” Because of the limited data available for MCI in PD, the practice implication is “ investigational .” Because of the lack of safety data, there is “ insufficient evidence ” to conclude on the safety of cognitive rehabilitation for cognitive impairment in PD.…”
Section: Results and Conclusionmentioning
confidence: 99%
See 1 more Smart Citation
“…One low‐quality, exploratory study evaluated cognitive rehabilitation for improving cognitive impairment in PD patients receiving computer‐based cognitive training; some significant effects were reported. Because of the exploratory character of the study and the small sample size, the efficacy conclusion is “ insufficient evidence .” Because of the limited data available for MCI in PD, the practice implication is “ investigational .” Because of the lack of safety data, there is “ insufficient evidence ” to conclude on the safety of cognitive rehabilitation for cognitive impairment in PD.…”
Section: Results and Conclusionmentioning
confidence: 99%
“…Because of the limited data available for MCI in PD, 34 the practice implication is "investigational." Because of the lack of safety data, 34,89 there is "insufficient evidence" to conclude on the safety of cognitive rehabilitation for cognitive impairment in PD.…”
Section: R E a T M E N T O F T H E N O N M O T O R S Y M P T O M S Imentioning
confidence: 99%
“…Seventeen reviews reported meta-analytic results for healthy older adults (Table 1), three of which focused specifically on individuals with subjective cognitive complaints (Bhome, Berry, Huntley, & Howard, 2018;Metternich, Kosch, Kriston, Harter, & Hull, 2010;Smart et al, 2017). Four reviews focused on individuals with MCI (Chandler, Parks, Marsiske, Rotblatt, & Smith, 2016;Sherman, Mauser, Nuno, & Sherzai, 2017;Wang et al, 2014). Ten reviews focused on people with dementia (Alves et al, 2013;Folkerts, Roheger, Franklin, Middelstadt, & Kalbe, 2017;Huntley, Gould, Liu, Smith, & Howard, 2015;Kim et al, 2017;Lee et al, 2019;P.…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
“…Six were classified as mixed COTs (Chandler et al, 2016;Lee et al, 2019;P. Leung et al, 2017;Rogers et al, 2018;Sherman et al, 2017;Yang et al, 2018), one of which focused specifically on COTs with caregiver involvement (P. Leung et al, 2017).…”
Section: Interventionsmentioning
confidence: 99%